Research progress of in-situ gelling ophthalmic drug delivery system - Wu, Yumei; Liu, Yuanyuan; Li, Xinyue; Kebebe, Dereje; Zhang, Bing; Ren, Jing; Lu, Jun; Li, Jiawei; Du, Shouying; Liu, Zhidong (Asian journal of pharmceutical sciences, 2019)
Blindness and vision impairment are the most devastating global health problems resulting in a substantial economic and social burden. Delivery of drug to particular parts of the anterior or posterior segment has been a major challenge due to various protective barriers and elimination mechanisms associated with the unique anatomical and physiological nature of the ocular system. Drug administration to the eye by conventional delivery systems results in poor ocular bioavailability (<5%). The designing of a novel approach for a safe, simple, and effective ocular drug delivery is a major concern and requires innovative strategies to combat the problem. Over the past decades, several novel approaches involving different strategies have been developed to improve the ocular delivery system. Among these, the ophthalmic in-situ gel has attained a great attention over the past few years. This review discussed and summarized the recent and the promising research progress of in-situ gelling in ocular drug delivery system. [Display omitted]